INCREASING THE CONFIDENCE OF CHILDREN AGED 4-5 YEARS THROUGH ROLE PLAYING - Rocmah, Luluk Iffatur (Journal of Higher Education and Academic Advancement, 2024)
Confidence in children aged 4-5 years should ideally be able to take part in learning without being awaited by their parents, be able to express opinions or wishes, be able to answer teacher questions, be able to carry out good activities related to themselves such as wearing their own shoes, as well as activities related to school, such as being able to write on your own, color on your own, cut and stick on your own. Children who have self-confidence can explore their abilities or potential, because they believe and have confidence in their abilities. Early childhood is a child aged 0-6 years who has development and growth that is more rapid and fundamental in the early years of life. This study aims to increase the self-confidence of children aged 4-5 years at Dharma Wanita Unity Kindergarten, Sidoarjo through role playing by starting with pre-cycle activities, then cycle 1 is carried out by obtaining a percentage of 62%, because the percentage does not meet the completeness criteria, it is carried out cycle II and obtained a percentage of 82% and met the targeted completeness criteria.